(untitled) (Journal of Contemporary Issues in Accounting, 2023)
This study was carried out to examine online tax adoption as an accountability tool on internally generated revenue in Abia State. In order to determine the relationship between online tax adoption and internally generated revenue, the study proxy online tax adoption using online direct tax assessment (ODTA) and online road taxes (ORT). The study adopted an ex post facto design and data were collected from the National Bureau of Statistics (NBS). Using Wilcoxon statistical test tool, the findings of the study indicate a positive and significant relationship between online direct tax assessment (ODTA), online road taxes (ORT) and internally generated revenue in Abia State Nigeria at 1% and 5% significant level respectively. Thus, the study concludes that the adoption of online taxes as a tool for accountability ensures and enhances internally generated revenue in Abia State. In lieu of the findings of the study, the study recommended the need for the adoption of online taxes which enhances the revenue generation of the state other than the former (manual collection) where most of the collected taxes and levies are not remitted to the government.